Clinical and Genetic Characteristics of Young Children with Fragile X Syndrome - So-Hee Lee; Ji-Eun Jeong; Yoon-Young Jang; Jin-Kyung Kim (Korean Child Neurology Society, 2021)
Purpose This study analyzed the clinical and genetic characteristics of young children with fragile X syndrome (FXS) and evaluated the significance of FXS genetic (FX) testing for children with global developmental delay (GDD). Methods FX testing was performed in 324 children aged <5 years and their family members between 2007 and 2020. Fourteen children (10 boys, four girls) with abnormal results were finally included in this report. We retrospectively reviewed their medical records and categorized them based on genetic test results. The results of an analysis of the expanded cytosine-guanine-guanine trinucleotide (CGG) alleles of fragile X mental retardation 1 (FMR1) were divided into four groups: normal, intermediate (IM), premutation (PM), and full mutation (FM). Results Twelve of the 14 children presented with FM (nine boys, three girls), and one each with PM and IM, respectively. Five of the children with FM and the one with PM belonged to two families. At the initial visit, the mean age of the nine boys with FM was 24.8±9.7 months. They presented with significant GDD and markedly delayed language development. Most of them had subtle physical features. Two girls with FM presented with less severe developmental delay than the boys with FM, and they were identified via sibling studies. However, one girl presented with FM resulting from maternal uniparental disomy and severe developmental delay. Conclusion Even in the absence of a family history, physicians should consider FX testing for children with unexplained GDD. If there is a family history of FXS, FX screening tests should be performed for all family members.